Neonatal Bacteremia Caused by Staphylococcus Epidermidis in Kirkuk City - Ahmed, Zahraa Ayid; Hassan, Ahmed Mahdi; Jalal, Mustafa J.; Abdulsalam, Rabia Khalid (American Journal of Bioscience and Clinical Integrity, 2026)
This study investigated cases of neonatal bacteremia and identified the causative agent in Kirkuk City. Eighty blood samples were collected from a cohort of neonates presenting with clinical signs of bloodstream infection who were admitted to the neonatal intensive care unit for sick and preterm infants. Staphylococcus epidermidis was isolated and identified based on morphological, biochemical, and physiological tests. Twenty-five (25) of the eighty samples (31.25%) yielded positive cultures. Antimicrobial susceptibility testing of selected isolates indicated susceptibility to vancomycin, amikacin, and teicoplanin, and demonstrated that penicillin was ineffective for the treatment of the bacteremia. The production of certain virulence factors by the isolates under study was also examined; the isolates differed in their ability to produce beta-lactamase enzymes and other virulence determinants.